ANALISIS YURIDIS PEMALSUAN IDENTITAS OLEH PENJUAL KARTU SUBSCRIBER IDENTITY MODULE INTERNET - Sinambela, Winda Handayani; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The establishment of criminal law is expected to be able to overcome legalproblems that occur in society. The existence of criminal sanctions is expected to have adeterrent effect on the perpetrators. If you look into Indonesian criminal law, there is noregulation on identity falsification carried out in electronic media, so there is no sanctionto the perpetrators. If the regulation on counterfeiting is not regulated, there will be manycases of identity forgery using electronic media. So that the value of the identity willdecrease and will cause many other crimes. Adami Chazawi in his book "Crimes RegardingCounterfeiting" said the attack on trust in the truth was in the form of an offense which wasdetermined as a crime. So, falsification of identity by an internet SIM card seller is anattack on trust and truth, because it contains elements of criminal acts, namely forgery(untruth).The purpose of writing this thesis is: First, to find out whether falsification ofidentity by the seller of an internet SIM card contains elements of illegal nature that can beaccounted for in criminal law. Secondly, to find out the ideal idea of legal regulation onidentity forgery by internet SIM card sellers.This type of research is normative legal research or can also be called doctrinallegal research. From the results of the research problem there are two main pointsconcluded, First, falsification of identity by internet SIM card sellers contains elements ofillegal nature, but in Indonesian criminal law there are no rules governing it so there areno sanctions that bind it. Therefore, a rule is needed which regulates the identity forgery.Second, the ideal legal arrangement related to identity forgery by internet SIM card sellersis that accountability can be requested to the perpetrator of identity forgery so that thevalue or significance of the identity can be maintained.